Achievement of low density lipoprotein (LDL) cholesterol targets in primary and secondary prevention: Analysis of a large real practice database in Italy. (June 2019) - Presta, Vivianne; Figliuzzi, Ilaria; Miceli, Francesca; Coluccia, Roberta; Fogacci, Federica; Cicero, Arrigo Francesco Giuseppe; Ferrucci, Andrea; Borghi, Claudio; Volpe, Massimo; Tocci, Giuliano; ,
Abstract: Background and aims: Target and intensity of low-density lipoprotein cholesterol (LDL-C) lowering therapy should be tailored according to the individual global cardiovascular (CV) risk. We aimed at retrospectively evaluating real-life LDL-C goal attainment and predictive factors for predefined LDL-C therapeutic goals both in primary and secondary prevention. Methods: We collected data from a large cohort of outpatients aged 40–65 years, followed by general practitioners, cardiologists and diabetologists in Italy. All data were centrally analysed for global CV risk assessment and rates of control of major CV risk factors, including LDL-C. Study population was stratified according to the presence or absence of previous CV events, including coronary artery disease (CAD), peripheral artery disease (PAD) or stroke/TIA. CV risk profile characterization was based on the European SCORE. Predefined therapeutic goals were set according to the European guidelines on dyslipidaemia: LDL-C levels <70 mg/dl for very high CV risk patients in primary prevention and for those in secondary prevention; <100 mg/dl LDL-C levels for high CV risk patients in primary prevention. Logistic regression analysis with clinical covariates was used to identify predictive factors for achieving these goals; lipid lowering therapy entered in the analysis as continuous (model 1) or categorical variable (model 2). Results: We included 4, 142 outpatients (43, 7% female, age 58.0 ± 5.2 years, BMI 28.5 ± 5.0 kg/m 2 ) among whom 2, 964 (71.6%) in primary and 1, 178 (28.4%) in secondary prevention. In primary prevention, none of the patients at very high CV risk had LDL-C <70 mg/dl and 8.9% of patients at high CV risk showed LDL-C <100 mg/dl. Only 5.8% of patients in secondary prevention had LDL-C levels <70 mg/dl, specifically 6.5% of patients with CAD, 2.6% of patients with PAD and 4.7% of patients with CVD ( p < 0.001). Beyond diabetes and lipid lowering therapy, high risk SCORE estimation resulted a strong and independent predictor for the lack of achieving all predefined therapeutic targets, including LDL-C <100 mg/dl [OR: 0.806 (0.751–0.865)); p < 0.001], and LDL-C <70 mg/dl [OR: 0.712 (0-576-0.880); p = 0.002], in primary prevention. Conclusions: Despite high or very high SCORE risk and use of lipid lowering therapies, we observed poor achievement of LDL-C targets in this large cohort of outpatients followed in a setting of real practice in Italy. Graphical abstract: Image 1 Highlights: Target and intensity of low-density lipoprotein cholesterol (LDL-C) lowering therapy should be tailored according to the individual global cardiovascular (CV) risk. Despite recommendations from international guidelines and recent evidence in favour of the beneficial effects derived from even intensive LDL-C reductions in very high risk patients, several observational studies and clinical surveys reported poor control rates of LDL-C in different clinical settings. We aimed at retrospectively evaluating real-life LDL-C goal attainment and predictive factors for predefined LDL-C therapeutic goals in adult outpatients in primary or secondary prevention. We observed relatively poor control rates of LDL-C in high or very high SCORE risk individuals in primary prevention and in very high risk outpatients with comorbidities in secondary prevention.